Salish Sea Chinook salmon exhibit weaker coherence in early marine survival trends than coastal populations. (5th June 2017) - Ruff, Casey P.; Anderson, Joseph H.; Kemp, Iris M.; Kendall, Neala W.; Mchugh, Peter A.; Velez‐Espino, Antonio; Greene, Correigh M.; Trudel, Marc; Holt, Carrie A.; Ryding, Kristen E.; Rawson, Kit
Abstract: Identifying factors that influence anadromous Pacific salmon ( Oncorhynchus spp.) population dynamics is complicated by their diverse life histories and large geographic range. Over the last several decades, Chinook salmon ( O. tshawytscha ) populations from coastal areas and the Salish Sea have exhibited substantial variability in abundance. In some cases, populations within the Salish Sea have experienced persistent declines that have not rebounded. We analyzed a time series of early marine survival from 36 hatchery Chinook salmon populations spanning ocean entry years 1980–2008 to quantify spatial and temporal coherence in survival. Overall, we observed higher inter‐population variability in survival for Salish Sea populations than non‐Salish Sea populations. Annual survival patterns of Salish Sea populations covaried over smaller spatial scales and exhibited less synchrony among proximate populations relative to non‐Salish Sea populations. These results were supported by multivariate autoregressive state space (MARSS) models which predominantly identified region‐scale differences in survival trends between northern coastal, southern coastal, Strait of Georgia, and Puget Sound population groupings. Furthermore, Dynamic Factor Analysis (DFA) of regional survival trends showed that survival of southern coastal populations was associated with the North Pacific Gyre Oscillation, a large‐scale ocean circulation pattern, whereas survival of Salish Sea populations was not. In summary, this study demonstrates that survival patterns in Chinook salmon are likely determined by a complex hierarchy of processes operating across a broad range in spatial and temporal scales, presenting challenges to the management of mixed‐stock fisheries.